Thoracic curlicue: A case of ureteral herniation - Sukumar, Sudhir (Medknow Publications, 2010)
Isolated herniation of ureter into thoracic cavity due to a defect in the diaphragm is a very rare entity. We present clinical details and radiographic images of an incidentally detected herniation of right ureter into the thorax in an elderly lady with no previous history of trauma or urinary tract symptoms. This acquired but asymptomatic condition is confirmed by radiologic imaging that reveals the classical loop configuration which is described as the curlicue sign. Further evaluation had revealed mild renal failure but with no definite evidence of obstruction. In view of age and asymptomatic status, patient was offered non-surgical management.